DNA e RNA polimerases do plasmídeo mitocondrial de moniliophthora perniciosa (Stahel) Aime & Phillips-Mora: caracterização, expressão, estudo de inibidores e filogenia molecular - Andrade, Bruno Silva (2011)
In this study we evaluated molecular and evolutionary aspects of DNA (DPO) and RNA (RPO) polymerases encoded by M. perniciosa mitochondrial plasmid. Three-dimensional models of these polymerases were constructed using a Homology Modeling approach, followed by Molecular Dynamics simulations of 3500 picoseconds. With modeled and validated 3D structures, we performed a virtual screening process in order to search for chemical compounds, using KEGG, ZINC and PubChem databases, followed by Molecular Docking (AutoDock Vina) and Molecular Dynamics MM/PBSA. Thus, we selected DPO-Entecavir and RPO-Rifampicin as the most stable complexes. The study of the relative expression of DPO and RPO genes was done by RT-qPCR, using cDNA from different developmental stages of M. perniciosa. In the phase of primordium, a significant increase in the activity of these genes occured, which is probably related to a self-defense process of the fungus against T. cacao. Phylogenetic analyses were performed by using DNA and protein sequences of DPO and RPO from M. perniciosa and other 12 fungal polymerases, as well as viral polymerases sequences. Then, Maximum Likelihood and Bayesian analyses were performed by using only fungal polymerase sequences, and the combination of fungal and viral polymerase sequences. Tree topologies results corroborate the hypothesis of Horizontal Gene Transfer (HGT) between fungal and viral polymerases, and delineate the evolutionary relationship of DPO and RPO M. perniciosa mitochondrial plasmid.